2022
DOI: 10.3280/mal2022-002003
|View full text |Cite
|
Sign up to set email alerts
|

Child Murder by Mothers: A Literature Review and a Call for Prevention

Abstract: In order to save children's lives, it is important to consider prevention of child homicide. Opportunities for prevention of neonaticide include increased access to sexual education, abortion, and prenatal care; vigilance of healthcare providers to risk factors, particularly lack of involvement in prenatal care; and engagement of psychiatric and social services when indicated. Safe Havens, baby boxes, and anonymous delivery may save lives. Regarding the killing of older infants, children, and adolescents, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Table 3 3,4,7,18,22,23 (page 18) describes the importance of understanding the motives for child murder by a parent in order to conceptualize appropriate prevention. Prevention efforts for 1 type of child murder will not necessarily help prevent murders that occur due to the other motives.…”
Section: Focusing On Preventionmentioning
confidence: 99%
“…Table 3 3,4,7,18,22,23 (page 18) describes the importance of understanding the motives for child murder by a parent in order to conceptualize appropriate prevention. Prevention efforts for 1 type of child murder will not necessarily help prevent murders that occur due to the other motives.…”
Section: Focusing On Preventionmentioning
confidence: 99%
“…These cases reflect a chilling trend that puts people at heightened risk of underreported abuse and neglect related to COVID-19 (MacNeil, 2020). And especially for children, abuse can easily become deadly when understanding that parental abusers are on average, more likely to kill their children under any conditions (Hatters et al 2007).…”
Section: Suicidality and Covid-19mentioning
confidence: 99%
“…That the media latches on to this stereotype in their coverage of infanticide and other child-killing stories is thus not surprising, given their propensity of adhering to simplified, mythical explanations (Motz, 2016). This is particularly noteworthy, as multiple studies have reported relatively low rates of mental health problems among women who have killed their newborns (e.g., Ciani & Fontanesi, 2012;Hatters et al, 2007;Lewis & Bunce, 2003), while prevalence rates among filicidal mothers tend to range between one-and twothirds (Poteyeva & Leigey, 2018). Despite this, the term mentally ill/insane was the most frequently used descriptor of filicidal mothers in Barnett's (2006) analysis.…”
Section: The Gendered Nature Of Infant Homicide Media Coveragementioning
confidence: 99%